Effect of ENERPLANT on the pepper's (Capsicum annuum, L) growth and output. - Osnil-Mois, Ing. Juan Emilio; Silva-Guirola, MSc. Dagnoris; Mois, MSc. Luis G.; Telo-Crespo, MSc. L Francisco; Iznaga-Labadie, Ing. yoelky (Hombre, Ciencia y Tecnología, 2018)
The study was developed during the period January – April, 2016, with the objective of determining ENERPLANT's most effective dose taking as a point of departure the evaluation of some variables of growth and performance, in the cultivation of the pepper; it was carried out an experiment with a randomed block design in the Agricultural Farm 1 in El Salvador, it was used the Español variety (Capsicum annuum Li.) and there were applied the doses 0.0 L•ha-1 as control, 0.0007 L•ha-1, 0.001 L•ha-1 and 0.0013 L•ha-1 of ENERPLANT; there were also used 10 kg m2 of bovine dung for all treatments. The results proved that the three treatments in which the product was applied had proper answers in relation to the control, taking into account the growth and performance of cultivation and being 0.0013. L•ha-1the most effective dose, which gave an utility of $ 91681.9.